Length of stay for tourists' inland trips. - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Correia, Marisol B. (Elsevier, 2018)
This paper addresses the problems of scant research on the Province of Malaga's interior and heterogeneous results of research on length of stay. Based on a negative binomial regression model and data from 675 surveys, the results suggest that two different patterns coexist simultaneously regarding variables’ impacts on the length of stay of national versus foreign tourists. For domestic tourists, their reasons for travelling condition length of stay, whereas, for international tourists, satisfaction has the most significant impact on length of stay. In addition, this paper confirms a negative relationship between income and length of stay. Implications for the tourism industry at the destination in question and possible future research are discussed
Keywords: Turismo; Málaga (Provincia) - Descripción y viajes; Caminito del Rey; Málaga; Inland tourism; Length of stay; Negative binomial model; Slow tourism